Comparison of holmium laser, bipolar and conventional monopolar transurethral resection of bladder tumour in primary non-muscle invasive bladder cancer - Salah Elmekawy; Diaa Eldin Taha; Hosam Eldeen Nabeeh; Ali Ibrahim; Ahmed Elsayed Zeid; Tarek abdelbaky (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the efficiency and safety profile of conventional monopolar, bipolar plasmakinetic and holmium laser techniques for transurethral resection of bladder tumour. Method: The prospective comparative study was conducted from July 2019 to May 2021 after approval from the ethics review committee of Kafrelsheikh University, Egypt, and comprised patients of either gender with primary nonmuscle invasive bladder cancer who qualified for transurethral resection of bladder tumour. The patients were stratified into low-risk group A, intermediate risk group B and high-risk group C in accordance with the guidelines of the European Association of Urology. Comprehensive cystoscopy and panendoscopy were done in all cases. Once panendoscopy was done, tumour resection was performed with monopolar resectoscope in group A, plasmakinetic resectoscope in group B and holmium laser in group C). Data was collected at preoperative, peroperative, postoperative and follow-up stages. Data was analysed using SPSS 21. Results: Of the 84 patients, 67(79.76%) were males and 17(20.23%) were females. There were 27(32.14%) patients in group A; 21(77.8%) males and 6(22.2%) females withy mean age 60.63±11.76 years. Group B had 32(38%) patients; 26(81.2%) males and 6(18.8%) females with mean age 65.34±7.55 years. Group C had 25(29.76%) patients; 20(80%) males and 5(20%) females with mean age 59.48±12.6 years. The mean follow-up period was 12.97±2.70 months in group A, 12.81±2.75 months in group B and 13.48±3.3 months in group C. Visualised complete resection was done in 23(85.8%) group A patients, 29(90.6%) group B patients and 24(96%) group C patients (p=0.018). Visualised complete resection, tumour multiplicity, tumour size, catheter duration, and hospital stay were significant predictors (p<0.05). Survival analysis showed 26(96.3%), 30(93.75%) and 25(100%) cases in groups A, B and C, respectively. Conclusion: Bipolar plasmakinetic and holmium laser techniques were found to be more effective and safer than the conventional monopolar technique for transurethral resection of bladder tumour in patients with primary non-muscle invasive bladder cancer. Keywords: Bladder neoplasms, Lasers, Prognosis, Urology, Catheters